Plotl earner’s Persuasive Achievement: Force, Flow and Context in Technology for Language Learning from the Hebrew Bible - Winther-Nielsen, Nicolai (HIPHIL Novum, 2014)
Kierkegaard’s manifesto for the art of helping focused on finding persons where they are and bringing them to the goal. This is also the goal of the learning technology PLOTLearner developed by EuroPLOT (www.eplot.eu). Using the text database of the Hebrew Bible from the Eep Talstra Centre for Bible and Computer (ETCBC) in Amsterdam, it offers both a simulation of Hebrew grammar and a tool for training language skills. The intended achievement is adapting to the context of learners while the corpus persuades learners to engage with persuasive forces that take them into the flow of learning. Using B. J. Fogg’s Computers as Persuasive Technology (2003), this paper presents the achievement of PLOTLearner in terms of persuasive functions, intrinsic motivation and potential outcome for learners. First, it refines persuasive principles by distinguishing between persuasive content, force and outcome, applying core distinctions from Searle’s Speech Act Theory. The persuasive principles subdivide into enablement and motivation, plus four orders of enhancing persuasive force. Secondly, Mihalyi Csikszentmihalyi’s theory of intrinsic motivation in flow developed into a new RAMP model inspired by Andrzej Marczewski, driving persuasive learning into a flow towards Relatedness through Autonomy and Mastery, once there is a commitment to Purpose. Third, the four core contexts for PLOTLearner are four expanding spaces which are learning objects. self-direction of learners, institutional facilitation, and social world. The strength of this open source technology is its ability to be repurposed to any corpus, language and learning culture. This is also its weakness, because flexibility calls for well-trained facilitators of this persuasive learning.